2011
DOI: 10.1007/s11244-011-9713-y
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of VO2(B) Nanoflake with Glycerol as Reductant Agent and its Catalytic Application in the Aerobic Oxidation of Benzene to Phenol

Abstract: Nanostructured VO 2 (B) was prepared by employing glycerol as reductant. Key parameters of the pH value of crystallization solution and the volume ratio of glycerol to water were optimized to prepare pure phase VO 2 (B). The VO 2 (B) could catalyze the aerobic oxidation of benzene to phenol with molecular oxygen in high selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Nanosystems comprising first‐row transition metals were mainly prepared under hydrothermal conditions. Mn II ‐based nanoparticles (Mn(OH) 2 , MnCO 3 )56 with diameters in the range 20–60 nm and VO 2 nanoflakes57 could be also prepared in glycerol/ethlylenglycol and glycerol/water mixtures, from KMnO 4 and V 2 O 5 , respectively, showing novel magnetic properties (for Mn II nanosystems) and catalytic applications in benzene oxidation to give phenol (for V IV nanoflakes). In both cases the ability of glycerol as stabilizer was underlined.…”
Section: Metal Nanoparticlesmentioning
confidence: 99%
“…Nanosystems comprising first‐row transition metals were mainly prepared under hydrothermal conditions. Mn II ‐based nanoparticles (Mn(OH) 2 , MnCO 3 )56 with diameters in the range 20–60 nm and VO 2 nanoflakes57 could be also prepared in glycerol/ethlylenglycol and glycerol/water mixtures, from KMnO 4 and V 2 O 5 , respectively, showing novel magnetic properties (for Mn II nanosystems) and catalytic applications in benzene oxidation to give phenol (for V IV nanoflakes). In both cases the ability of glycerol as stabilizer was underlined.…”
Section: Metal Nanoparticlesmentioning
confidence: 99%
“…32,33 The corresponding adsorption/desorption processes mainly take place on the surface of the sensing layer; therefore, nanostructures with a higher surface to volume ratio is prone to provide more surface activity resulting in a better sensing performance. Within the V-O systems, most of the sensing studies reported in the literature focus on V 2 O 5 , whereas reports concerning the sensing properties of VO 2 are rare; even though recent studies have emphasized on the catalytic activity of VO 2 (B) 34,35 establishing excellent surface activity for this metastable phase of VO 2 . Among the handful of reports in the literature citing its sensing property, Micocci et al 36 have investigated vanadium oxide thin films for an ethanol sensor.…”
Section: Introductionmentioning
confidence: 99%
“…The yield of phenol maintained at about 2.6%. The result increased compared with that of bulk VO 2 (B) [29] or other studies [17−20], which was usually less than 1% in the absence of reductant. …”
Section: Uv-vis and Uv-vis-nir Spectramentioning
confidence: 57%
“…VO 2 has the property of being oxidized to V 2 O 5 (standard reduction potentials at 25 • C, +1.00 V) and being reduced to V 2 O 3 (standard reduction potentials at 25 • C, +0.36 V), and thus has the advantages of electrical applications, optical applications and catalytic reactions [29]. We ever prepared metastable VO 2 (B) nanoflake using a reduction method by hydrothermally treating V 2 O 5 with glycerol [29]. The VO 2 (B) nanoflake was employed as catalyst in hydroxylation of benzene to phenol with molecular oxygen and high selectivity to phenol was obtained.…”
Section: Introductionmentioning
confidence: 99%